Draft Five Year Plan 1980-85 Part-I Outline Union Territory of Delhi - Planning Commission (Planning Commission, 1980)
The total geographical area of the Union Territory of Delhi is 1485 Sq. Kms. It is predominently urban in character and is also capital of the country. On account of those factors and other peculiar characteristics of this territory, the needs and priorities of Delhi are different from those of other states and Union Territories. Accordingly emphasis in the plan is ahead on providing social services and civic amenities particularly under the sectors of Power, Water Supply and Sewerage, Transport and Communication, Education, Housing, Urban Development and Medical.
Planning Department, Delhi Administration